Programming Windows Workflow Foundation : practical WF techniques and examples using XAML and C♯ : a C♯ developer's guide to the features and programming interfaces of Windows Workflow Foundation /: practical WF techniques and examples using XAML and C♯ : a C♯ developer's guide to the features and programming interfaces of Windows Workflow Foundation. (2006) - Unknown
No abstract available